The Phytoextraction of Copper from Tropical Soil 21 Years after Amendment with Heavy-Metal Containing Waste - Gianluigi Silva; Septi Nurul Aini; Henrie Buchari; Abdul Kadir Salam (JOURNAL OF TROPICAL SOILS, 2021)
Several particular plants are suggested to extract significant parts of heavy metals from soils and accumulate them in their roots and shoots.  This research aimed to study the phytoextraction of Cu by several plants from heavy-metal contaminated tropical soils.  Soil samples collected from plots treated in 1998 with 0, 15 and 60 Mg industrial waste ha-1 were planted with three different plants, i.e., caisim, water spinach, and lettuce.   Plant parts (roots and shoots) and soil samples were harvested after a four-week growth period and analyzed for plant and soil Cu.  The results show that the growth of plants was depressed by the increase in the soil Cu (extracted by 1 N HNO3) as affected by waste levels, with water spinach being the most progressive and produced the most significant biomass.  The absorption of Cu by caisim and water spinach increased with the soil extracted Cu (linear R2 = 0.71* for caisim and 0.32* for water spinach) and accumulated greater in plant roots than that in shoots. The translocation factor (TF << 1.00) indicates that all plants were good Cu phytostabilizators rather than phytoextractors, with water spinach being the best Cu extractor.